Issues of Geoinformation Technology and Remote Sensing in the Creation of Land Cadastres - Maharramli, Z.S. (Herald of Azerbaijan Engineering Academy, 2025)
The main purpose of the article is to consider the traditional data structure of a geographic information system and highlight the interconnected cartographic and attribute components in it. It consists of analyzing the results obtained as a result of color digital aerial photography of an area of 2,350 km2 in the cities of Baku and Sumgait.